Bamboo arch, Port of Spain, Trinidad, B.W.I. - Strong, H. (My University, 2010)
Shows an automobile passing under the bamboo arches on the way to St. Anns.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Suburbs--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. Ann's; Bamboo--Trinidad and Tobago